Mobile ad-hoc and sensor networks third international conference, MSN 2007, Beijing, China, December 12-14, 2007 : proceedings - International Conference on Mobile Ad-Hoc and Sensor Networks (Lecture notes in computer science, 2007)
Keynote speech -- Routing -- Protocol -- Energy efficiency -- Data processing -- Self-organization and synchronization -- Deployment and application -- Security.